Mission As God's Spiral of Renewal. - Ross, R (Mzuni Press, 2019)
Cover -- Copyright page -- Title page -- Dedication -- Contents -- Acknowledgements -- Introduction -- 1. "Blessed Reflex": Mission as God's Spiral of Renewal -- 1) Recognise that mission and the mission field have completely changed. -- 2) Recognise that we are always the recipients as well as the agents of mission. -- 3) Cultivate the sense of adventure that is essential to authentic Christian mission. -- 2. "Give us Friends!" The Relational Dimension of Christian Mission -- Friendship at the Heart of the Missionary Movement -- A Case Study: Scots and Malawians -- A World Crying out for Friendship: Christian Mission in the Twenty-first Century -- I Have Called You Friends": Mission in the Way of Jesus -- 3. Like a Mask Dancing: Partnership in Mission Entersa New Mode -- Introduction: from Partnership to Twinning -- New Eyes to Read the New Testament -- The Place of Twinning in the Transformative Purpose of God -- Conclusion -- 4. Beyond Religious Tourism: Twinning as a Missionary Method -- Mere Religiously Themed Tourism? -- Western Indulgence Imposing on Non-Western Partners? -- Communication Failure -- The "Love Miles" Dilemma -- Inter-Church Aid rather than Mission? -- 5. Releasing First-World Wealth for Global Mission: What Levers can be Pulled Today? -- Introduction: Mission and Money -- Church Decline in the West -- A New Parochialism -- A Consumerist Lifestyle -- Project Orientation -- Soteriological Relativism -- More Sophisticated Models of Mission -- Levers to Pull -- The Great Commission: An Uncancelled Mandate -- Justice for the Poor -- Catholicity and Mutuality -- Local Initiative and Direct Involvement -- Conclusion -- 6. The HIV/AIDS Pandemic: What is at Stake for Christian Mission? -- Introduction -- Humanity at Stake - Justice and Compassion -- The Church at Stake - New Frontiers for Faith.